(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of our study was to determine the levels of ESR and CRP in psoriasis with/without psoriatic arthritis and to find whether there is any correlation of their values with its severity and presence or absence of psoriatic arthropathy. Study Design: Prospective study. Place and Duration of Study: This study was conducted at Jinnah Postgraduate Medical Centre, Karachi from January 2014 to August 2014. Materials and Methods: 60 patients, 35 males and 25 females were enrolled. After detailed history and severity assessment by PASI, blood was sent for ESR and CRP levels. All data was documented and analyzed. Result: There were 60 patients (35 males and 25 females) with age ranging from 20-65 years and had a history of psoriasis from 1-38 years. 89% had chronic plaque psoriasis and 30% had psoriatic arthropathy. PASI score ranged from 4-26 (Mean 7.92±6.38). The means of ESR and CRP were 16.44 ± 12.66 mm/hr and 3.84±3.63 mg/L respectively. Neither ESR nor CRP levels directly correlated with PASI or with psoriatic arthropathy. Conclusion: ESR and CRP doesn’t seem to have prognostic significance in mild to moderate psoriasis and psoriatic arthropathy. However there might be any role of ESR or CRP. in patients with severe psoriatic arthropathy.